GAMBARAN KECEMASAN DENTAL ANAK PADA KEGIATAN TUR EDUKASI DENTAL ANAK KE RSIGM-SA - Amalina, Rizki; Agusmawanti, Prima; Rizkika, Nabila; Muchaeroni, Isa Anshori (Jurnal Pengabdian Masyarakat DentMas, 2024)
Background: The Indonesian Health Survey states that oral health problems in the population aged ≥ 3 years are still high. Dental care is important requirement for the maintenance of children's health. One of the psychological problems that often occurs in children when undergoing dental treatment is anxiety. Anxiety towards dental care is also called dental anxiety. To overcome this anxiety can be done by fun learning education through field trip study. Field trip study aims to introduce children to real life, provide new experiences and make it an interesting place to learn.Objective : Targeting kindergartens and early childhood schools aims to invite the school community to think, behave and act to build and develop themselves to care with their dental and oral health.Method: In this community service activity, children are invited to take an educational tour to the Islamic Dental Hospital-Sultan Agung (RSIGM-SA) to recognize oral health facilities, increase knowledge about oral health and reduce dental anxiety in children.Result: Children's dental anxiety level evaluation after conducting an educational tour at RSIGM-SA, showed that the majority of children have a low level of anxiety with a high level of knowledge about oral health.Conclusion: Educational tours can be one of the concrete applications of Tell-Show Do method in children oral health management.